Analysis of public participation in public hearings during the environmental licensing process of Nova Ferroeste - Portes, José Alex; Miranda Abreu, Simone de Paula; Lemos Jucá, Henrique Cesar; Laranja, Ruth Elias de Paula (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
Public participation in Environmental Licensing is essential and is primarily expressed through Public Hearings conducted prior to project implementation. Although these are not deliberative spaces, the public has the freedom to present criticisms or suggestions, influencing the licensing authority’s decision-making process. Through an exploratory documentary study with a qualitative approach, this research aims to analyze the contributions arising from the Public Hearings held by Ibama during the environmental licensing process for the 'Nova Ferroeste' railway project, located between the states of Mato Grosso do Sul and Paraná. Approximately 3.000 participants attended the seven hearings conducted, with 184 statements or remarks recorded, divided into 416 interventions or topics addressed, including questions, requests, or the presentation of information. Due to the project's large scale, varying public interests were observed depending on the region affected. Three main themes emerged as key concerns for participants: the crossing of the Serra do Mar mountain range, the impacts on small properties in the São José dos Pinhais/PR region, and the effects on traditional communities in the Dourados/MS region. Despite criticisms about the effectiveness of the current format of public hearings, allegedly due to their limited capacity to influence decision-making, it is concluded that analyzing social participation and the contributions received—particularly the three aforementioned themes—supported the technical feasibility analysis of Nova Ferroeste and the decision to return the initial version of the EIA/RIMA. This underscores the importance of this instrument in assessing the feasibility of projects with significant socio-environmental complexity.